Elevated levels of TWEAK in skeletal muscle promote visceral obesity, insulin resistance, and metabolic dysfunction. Issue 3 (2nd December 2014) - Sato, Shuichi; Ogura, Yuji; Tajrishi, Marjan M.; Kumar, Ashok
Abstract : Skeletal muscle is responsible for the majority of glucose disposal in body. Impairment in skeletal muscle glucose handling capacity leads to the state of insulin resistance. The TNF‐like weak inducer of apoptosis (TWEAK) cytokine has now emerged as a major regulator of skeletal muscle mass and function. However, the role of TWEAK in skeletal muscle metabolic function remains less understood. Here, we demonstrate that with progressive age, skeletal muscle‐specific TWEAK‐transgenic (TWEAK‐Tg) mice gain increased body weight (~16%) and fat mass (~64%) and show glucose intolerance and insulin insensitivity. TWEAK‐Tg mice also exhibit adipocyte hypertrophy in the epididymal fat. Oxygen uptake, voluntary physical activity, and exercise capacity were significantly reduced in TWEAK‐Tg mice compared with controls. Overexpression of TWEAK inhibited (~31%) 5' AMP‐activated protein kinase (AMPK) and reduced (~31%) the levels of glucose transporter type 4 (GLUT4) without affecting the Akt pathway. TWEAK also inhibited insulin‐stimulated glucose uptake (~32%) and repressed the levels of GLUT4 (~50%) in cultured myotubes from C57BL6 mice. TWEAK represses the levels of Krüppel‐like factor 15; myocyte enhancer factor 2, and peroxisome proliferator‐activated receptor‐γ coactivator‐1α, which are required for the activation of the GLUT4 locus. Collectively our study demonstrates that elevated levels of TWEAK in skeletal muscle cause metabolic abnormalities. Inhibition of TWEAK could be a potential approach to prevent weight gain and type 2 diabetes.—Sato, S., Ogura, Y., Tajrishi, M. M., Kumar, A., Elevated levels of TWEAK in skeletal muscle promote visceral obesity, insulin resistance, and metabolic dysfunction. FASEB J. 29, 988–1002 (2015). www.fasebj.org